Figurative Language Used In Olivia Rodrigo Album Song Lyrics “Sour” - Natalya Helena Susanty Izym; Ni Wayan Suastini (CV. Multi Kreasi Media, 2023)
Fascinating phrases have distinct connotations, including the usage of figurative language to describe thoughts in song lyrics. This research examined at the metaphorical language of an Olivia Rodrigo song's lyrics. The study's objective is to determine the different forms of figurative language contained in Olivia Rodrigo Songs and examine the meaning of figurative speech in Olivia Rodrigo Songs from Album “Sour”. In the analysis, Sour is the debut studio album by Olivia Rodrigo, an American singer-songwriter. It was released by Geffen Records on May 21, 2021. Rodrigo wrote the album with producer Dan Nigro and recorded it during the Covid-19 pandemic lockdown seclusion. Ffigurative refers to the use of words in ways that deviate from their traditional order or meaning to convey complex meaning, fascinating sentences, clarity, or evocative comparisons. Use regular phrases refer to something without saying it directly. The data were taken from Olivia Rodrigo Songs. Knickerbocker and Reninger's (1963) theory was utilized to analyse the data, while Leech (1981) and Johnson (2003:4) theory was used to examine the meaning of figures of speech employed. The analysis was done by applying descriptive qualitative and quantitative methods with observation and noted taking techniques to acquire data. This study discovered there were 4 categories of figurative language and 2 forms of figurative meaning.